Acute Coronary Syndrome in Young Adults: Beware of an Anomalous Origin of the RCA - Paris, Francois MA; Schuurman, Robert J; Jessurun, Gillian AJ; Anthonio, Rutger L; Mariani, Massimo A (Cardiology and Cardiovascular Medicine, 2020)
Cardiologists and cardiac surgeons may have the clinical conception that the contralateral rudimentary vessel in a left or right dominant coronary tree should not be revascularised because of its nonsignificant myocardial blood supply. We would like to highlight and argue that this conception should be challenged in subjects with ischemia driven life threatening arrhythmias caused by the anomalous course of the rudimentary artery. Hereby we would like to contribute to the appropriate clinical approach of young subjects with an acute coronary syndrome. We describe two young patients with an Acute Coronary Syndrome who appear to have an anomalous rudimentary right coronary artery. These cases may suggest that even in a left dominant coronary system an anomalous origin of the RCA can be life threatening. Surgery should be considered at the time that this symptomatic anomaly is identified.